Atopic Dermatitis in a Bitch - Association of Cyclosporin and Cannabis Oil - Mariga, Carollina; Schiefler, Otávio Henrique de Melo; Nauderer , Jelson Norberto; da Silva, Ana Paula; Bottari, Nathieli Bianchin; Flores, Mariana Martins; Schmidt, Claudete; Pinto Filho, Saulo Tadeu Lemos (Acta Scientiae Veterinariae, 2024)
Background: The endocannabinoid system (eCBoma) is a complex of interactions between endocannabinoid substances, enzymes, and various receptors present throughout the body. In this way, cannabis therapy, comprising phytocannabinoids, represents a therapeutic potential much researched in other areas, but still scarce in veterinary medicine. We highlight the potential use of this therapy in dogs with atopic dermatitis, the second most common allergic skin disease in clinical routine and which represents a therapeutic challenge for controlling clinical signs. The objective of this work is to report a case of the association of Cannabis oil with ciclosporin in a bitch. Case: A 8-year-old mixed breed spayed bitch, with a previous diagnosis of atopic dermatitis and a history of therapies with inefficient results was attended at the Veterinary Medical Teaching Hospital of the Federal University of Santa Maria (UFSM), Santa Maria, RS, Brazil. During the consultation, the profile of oxidative stress and skin histopathology were assessed, with mast cell count to assess the effectiveness of the association, in addition to the measurement of blood glucose and systolic blood pressure, and blood collection to perform blood count and biochemical profile to evaluate the effectiveness of the treatment used. Another form of evaluation applied was the owner’s perception of the animal’s adaptation to the new treatment, with regard to itching, skin lesions, and adverse effects, through a questionnaire. As treatment, ciclosporin was prescribed at a dose of 1.25 mg/kg, SID in association with Cannabis oil “full spectrum high” cannabidiol (CBD) 4%, 8 drops once a day for 60 days. Baths with chlorhexidine shampoo were maintained. According to the owner's perception, the animal presented good acceptance to the treatment, reporting drowsiness, hyperexia, weight gain, and calmer behavior as adverse effects, which were not harmful to the animal, and did not require that the treatment be interrupted. A decrease in blood glucose levels, an increase in antioxidant substances and a decrease in itching were observed. Discussion: Canine atopic dermatitis is characterized as an allergic skin disease, most frequently diagnosed in dogs, with a multifactorial pathogenesis and challenging to control, requiring the use of continuous treatment throughout the patient's life. The most commonly used commercial treatment option is ciclosporin. Ciclosporin is a calcium-inhibiting medication that binds to the cytoplasm of lymphocytes and inhibits the translocation of nuclear factor from activated T cells to the nucleus, negatively regulating the synthesis of several cytokines, such as IL-2 and IFNγ. The CB1 and CB2 receptors of the endocannabinoid system are located in different parts of the body, including the skin, with functions of maintaining the skin barrier, cell growth and differentiation, and immunological and inflammatory processes. The particularity of the eCBoma in the skin is a growing therapeutic target. Its receptors, present in specific skin cells, become targets of different therapies in different diseases that affect the largest organ of the body, mainly due to their anti-inflammatory, antioxidant, and analgesic properties. Not only present in the skin, this system influences different mechanisms, such as blood glucose regulation, systemic pressure, and increased antioxidant substances in the body. It is concluded that Cannabis oil is promising when combined with ciclosporin in order to control the clinical signs of canine atopic dermatitis, thus improving the patient's quality of life. Keywords: antioxidant, atopic, ciclosporin, Cannabis therapy. Título: Dermatite atópica em uma cadela - Associação de ciclosporina e óleo de Cannabis Descritores: antioxidante, atopia, ciclosporina, terapia canábica